2016
DOI: 10.1039/c5sc04287a
|View full text |Cite
|
Sign up to set email alerts
|

Snapshots of a solid-state transformation: coexistence of three phases trapped in one crystal

Abstract: Solvent extrusion leads to crystallographic–magnetic transition within a molecular complex via an intermediate that can be trapped and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 44 publications
(47 reference statements)
1
44
1
Order By: Relevance
“…[46] It has been identified in several instances before, sometimes involving helicates [22] or severalo ther discrete dinuclear complexes. [47][48][49] However,t his well-defineds pin mixing is not limited to [Fe 2 ]m olecules.I tc an be found in mononuclear systems, [50,51] in clusters of other nuclearities, [14,52,53] or in coordination polymers. [54,55]…”
Section: Thermal Spin-crossover Propertiesmentioning
confidence: 99%
“…[46] It has been identified in several instances before, sometimes involving helicates [22] or severalo ther discrete dinuclear complexes. [47][48][49] However,t his well-defineds pin mixing is not limited to [Fe 2 ]m olecules.I tc an be found in mononuclear systems, [50,51] in clusters of other nuclearities, [14,52,53] or in coordination polymers. [54,55]…”
Section: Thermal Spin-crossover Propertiesmentioning
confidence: 99%
“…To our knowledge, a result of this entirely unexpected nature has not previously been characterized in detail for a molecular crystal. A case of several structures being characterized from the same sample has been reported recently (Aromí et al, 2016). The difference in the present case is that the crystal remained stable with its two components at 170 K and, furthermore, despite a good deal of reflection overlap it was possible to isolate complete redundant individual data sets for both components using in-house data.…”
Section: Arrested Phase Transitionmentioning
confidence: 70%
“…In addition, crystals of nonporous molecular materials have also been reported to show crystalline solid transformations through chemical reactions with gases despite the difficulty of maintaining crystallographic cohesion . In fact, it has even been reported the structural determination of an intermediate phase during a chemical transformation in a non‐porous molecular solid . We recently demonstrated that the combination of cooperative magnetism and gas sorption can be easily achieved through the use of nonporous materials able to incorporate the gas molecules into its framework, thus alleviating the necessity of large pores .…”
Section: Introductionmentioning
confidence: 99%
“…In these magnetic crystalline materials, the desired long structural order is preserved despite the rearrangement suffered, including cleavage and formation of covalent bonds, although the single crystal nature of the solid is typically lost, thus resulting in polycrystalline powders. Indeed, magnetic materials with structures unequivocally characterized by single‐crystal diffraction after a chemical reaction are tremendously valuable for understanding the mechanism of the transformation and the magnetostructural correlations, but are extremely scarce …”
Section: Introductionmentioning
confidence: 99%